Jung, Schopenhauer and the Problem of Evil - Garralaga Foronda, Alejandra (Logos. Anales del Seminario de Metafísica, 2023)
Much has been said about the influence of Eastern religions on Arthur Schopenhauer’s thought, and very little about the latter’s impact on one of the less recognized thinkers in academic philosophy, namely Carl Gustav Jung. The present paper attempts to draw a common ground between both authors, highlighting analogies as well as discrepancies between the Schopenhauerian «Will» and the Jungian «Unconscious», while deepening the central locus that links, as we argue, both thought systems: the problem of evil and its different formulations in Eastern religions and in the Christian West.
Keywords: Jung; Schopenhauer; problem of evil; religion; Buddhism; Christianism; privatio boni; Unconscious; Will; metaphysics